Effect of dietary supplementation of Euglena viridis on growth performance and selected serum biochemical parameters in Labeo rohita (Hamilton, 1822) fingerlings - Pradhan, Jyotirmayee; Sahu, Swagatika; Nayak, Kausalya K.; Das, B. K. (Indian Journal of Fisheries, 2021)
Fingerlings of Labeo rohita (Hamilton, 1822) (25±2 g) were fed on Euglena viridis supplemented diets @ 0 (Control), 0.1 g kg-1, 0.5 g kg-1 and 1.0 g kg-1 for 90 days. At 30 days intervals, blood serum samples were assayed for glucose level and enzymatic parameters viz., serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), acid phosphatase (ACP) and alkaline phosphatase (ALP). Fish were challenged with a virulent strain of Aeromonas hydrophila after 90 days feeding period. Insignificant (p>0.05) differences in serum AST levels were noticed on the 30th and 60th day of feeding between the different dietary groups of fish. Serum enzymes (ALT, AST and ALP) significantly (p<0.05) declined in fish fed on E. viridis incorporated diets. On the 10th day post-challenge with A. hydrophila, the highest percentage of survival (75%) was recorded in the dietary group fed with 0.5 g kg-1 E. viridis. The best feed conversion ratio (FCR) and highest specific growth rate (SGR) were recorded in the group fed with 0.5 g kg-1 E. viridis incorporated diet. The results clearly indicated that dietary E. viridis promote growth rate and decreases susceptibility to A. hydrophila and did not negatively impact serum enzyme levels in L. rohita . Keywords: Aeromonas hydrophila, Alanine aminotransferase (ALT), Alkaline phosphatase (ALP), Aspartate aminotransferase (AST), Euglena viridis, Labeo rohita